2003
DOI: 10.1002/anie.200300579
|View full text |Cite
|
Sign up to set email alerts
|

Highly Functionalized Organomagnesium Reagents Prepared through Halogen–Metal Exchange

Abstract: Organomagnesium reagents occupy a central position in synthetic organic and organometallic chemistry. Recently, the halogen-magnesium exchange has considerably extended the range of functionalized Grignard reagents available for synthetic purposes. Functional groups such as esters, nitriles, iodides, imines, or even nitro groups can be present in a wide range of aromatic and heterocyclic organomagnesium reagents. Also various highly functionalized alkenyl magnesium species can be prepared. These recent develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
320
0
4

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 764 publications
(332 citation statements)
references
References 215 publications
2
320
0
4
Order By: Relevance
“…The synthesis of 4-carboxy-Pennsylvania Green (6) was accomplished in 10-steps from commercially available 1,2,4-trifluoro-5-nitrobenzene (7). As shown in Scheme 1, 1-amino-2,4-dimethoxy-5-fluorobenzene (9) was prepared via 8 by a previously reported route.…”
Section: Nih Public Accessmentioning
confidence: 99%
“…The synthesis of 4-carboxy-Pennsylvania Green (6) was accomplished in 10-steps from commercially available 1,2,4-trifluoro-5-nitrobenzene (7). As shown in Scheme 1, 1-amino-2,4-dimethoxy-5-fluorobenzene (9) was prepared via 8 by a previously reported route.…”
Section: Nih Public Accessmentioning
confidence: 99%
“…However, it was found that yields of this series of copolymer were relatively low. Hence, it is suggested that for the synthesis of this series of copolymers, other Grignard regents such as isopropylmagnesium chloride (i-PrMgCl) or isopropylmagnesium bromide (i-PrMgBr) together with lithium chloride (LiCl) may be used to afford the copolymers in good yields [29,30]. Since the copolymer synthesized by Wei's group comprising of equal molar ratio of M1!…”
Section: Instrumentationmentioning
confidence: 99%
“…If Grignard reagents are to be used as nucleophiles in coupling reactions with aryl bromides or chlorides it has been shown that lithium halide adducts of the Grignard reagents show an enhanced reactivity. [54][55][56][57][58] The aim of this research therefore was to gain an understanding of the mutual effects of various transition metals, different spectator ligands, lithium halide additives and the substitution pattern of the respective bromobenzene derivative on the efficiency of the cross-coupling reaction. Moreover, we were highly interested to find a synthetic protocol that allows for the use of iron catalysts with yields that should be comparable to the very well working palladium catalysts.…”
Section: Introductionmentioning
confidence: 99%